High-Dose Glucocorticoid Therapy in the Management of Seizures in Neonatal Incontinentia Pigmenti: A Case Report. (January 2015) - Wolf, David S.; Golden, W. Christopher; Hoover-Fong, Julie; Applegate, Carolyn; Cohen, Bernard A.; Germain-Lee, Emily L.; Goldberg, Morton F.; Crawford, Thomas O.; Gauda, Estelle B.
Incontinentia pigmenti is an X-linked dominant disorder resulting from a mutation of IKBKG . This disorder has a classic dermatologic presentation, but neurologic involvement, with seizures and cortical infarction, can arise shortly after birth. There are no specific therapies available for the manifestations of incontinentia pigmenti. Here, we describe the clinical, electrographic, and neuroradiologic effect of systemic glucocorticoid therapy in a neonate with incontinentia pigmenti manifesting an epileptic encephalopathy. Treatment with dexamethasone led to a dramatic reduction in seizure activity and improvement in bullous lesions. A novel mutation in IKBKG is also reported.